Climatic Signals Derived from the Growth Variation and Cycles of Pinus merkusii in Easternmost Thailand - Duangsathaporn, Khwanchai; Palakit, Kritsadapan (วารสารวนศาสตร์ไทย, 2022)
Pinus merkusii is one of tropical tree species that have been proven for dendroclimatic studies. In the last 10 years, most of the tree-ring research on P. merkusii has focused on the northern region of Thailand. Our study site was a pine stand located on a rock cliff in the easternmost region of Thailand (latitude 150 31’N and longitude 1050 37’ E). In early 2009, 66 cores from 30 P. merkusii trees were collected and prepared following standard dendrochronology methodology. A tree-ring chronology was constructed covering the period 1881-2008, with excellent crossdating properties over most of that interval. Based on this tree-ring chronology, most notable below-average growth was during the period 1960s – 1990s. Except the growth before this interval and the last decade in this period, growth variations were close to the average. The last decade data showed an increasing growth trend above the average. Spectral analysis indicated the cycle of growth variability in easternmost Thailand merkus pines for 3.8-4.7 years. An analysis of the local climatic signals on tree-ring chronology indicated a strong relationship of pine growth with current year rainfall at the beginning of wet season and with previous year temperature during the transitional period of wet and dry season. An analysis of regional climatic signals indicated that tree-ring index was correlated with Equatorial Southern Oscillation Index (SOI) and Tropical Pacific Sea Surface Temperature (SST). The results indicated a positive response to SOI in September of the previous year, and indicated a negative response to SST in August of the previous year. From this study, we can conclude that the long term variation both of local and regional climatic signals can be determined using the radial growth of P. merkusii from the easternmost Thailand. Keywords: Pinus merkusii, Merkus pine, Tropical Pacific SST, Equatorial SOI, Dendroclimatology, Tree-ring chronology, Thailand, Spectral analysis